Axonal loss in multiple sclerosis: a pathological survey of the corticospinal and sensory tracts. - DeLuca, G; Ebers, G; Esiri, M (2004)
Clinical, imaging, and pathological studies in multiple sclerosis have generally emphasized the relative preservation of axons in comparison with myelin. Recent evidence, however, demonstrates that axonal loss is also significant, affects long tracts such as the corticospinal and sensory tracts and relates closely to functional disability. Accordingly, the distribution and extent of this axonal loss is the focus of the current investigation. Post-mortem material of 55 multiple sclerosis patients and 32 matched controls was used to examine quantitatively the population of axons in the corticospinal tracts from the medulla to the lumbar spinal cord and the sensory tracts from the lumbar to the upper cervical spinal cord. Myelin- and axon-stained sections have been prepared to estimate the notional area and axon density, respectively of both tracts. Our results indicate that in the corticospinal tracts there is a significant reduction of the area and axon density at all levels investigated in multiple sclerosis cases when compared with controls. In contrast, the sensory tracts in multiple sclerosis cases showed a significant reduction in area and axon density only in the upper regions of the spinal cord. As has been found with MRI plaque load and T2 burden, correlations of axonal loss with duration of disease were not strong. Of the fibres lost in multiple sclerosis, we have found that small fibres (<3 microm2) seem to be particularly affected, with large fibres remaining relatively preserved in both the corticospinal and sensory tracts. In multiple sclerosis, axonal loss is widespread, and its extent is tract specific and size selective.